Transforming lives of people with intellectual disability - Special Olympics Australia (Special Olympics Australia, 2013)
Colour lithographic poster promoting Special Olympics Australia, an organisation which caters only to people with an intellectual disability, with a focus on weekly sports participation in local communities. By providing meaningful sports programs delivered within a supportive environment, people with an intellectual disability are accepted and can feel proud of their achievements. For some involvement gives a chance to get active, have fun, make friends and be part of a family. Others enjoy the competition pathways and aim to participate in the Special Olympics World Games which are hosted every two years alternately in both summer and winter sports. The main image is a young female athlete wearing a Special Olympics medal on a yellow ribbon round her neck. On her face she has three temporary stamps with the logo and wording Special Olympics South Australia. In the background other athletes are standing on the athletics track. The caption at the top in white text, is in a green banner. Other information about the organisation is in a green box in the bottom right of the poster.
Caption title.
"www.specialolympics.com.au"--At foot of poster.
Keywords: Sports for people with mental disabilities -- Australia; Sports for people with disabilities -- Australia; Sports posters -- Australia; Sports posters -- Australia; Posters, Australian; Australia -- Posters; Australian